Mszał Kraśnicki – zabytek z XV wieku - Moskal, Tomasz (Archiwa, Biblioteki i Muzea Kościelne, 2017)
Kraśnik missal – liturgical manuscript dated for the beginning the 15th century, probably product scriptorium by the monastery of Canons Regular in Cracow. In the 16th century his presence authenticated at the monastery in Kraśnik. In the XIX century transported to the seminar library in Lublin. He consists of two parts, containing the calendar of the Cracow diocese and liturgical texts among others.